2009
DOI: 10.1093/hmg/ddp421
|View full text |Cite
|
Sign up to set email alerts
|

Mutant SOD1 in neuronal mitochondria causes toxicity and mitochondrial dynamics abnormalities

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder characterized by motor neuron degeneration. Mutations in Cu,Zn-superoxide dismutase (SOD1) are responsible for 20% of familial ALS cases via a toxic gain of function. In mutant SOD1 transgenic mice, mitochondria of spinal motor neurons develop abnormal morphology, bioenergetic defects and degeneration, which are presumably implicated in disease pathogenesis. SOD1 is mostly a cytosolic protein, but a substantial portion is associated with orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 46 publications
5
118
0
Order By: Relevance
“…2C). Consistent with the axonal transport defects observed in embryonic motor neurons and adult DRG neurons (10,11,16), axonal mitochondria in SOD1 G93A DRG neurons showed reduced mobility (13.54 Ϯ 0.38%, mean Ϯ S.E. ), anterograde transport (10.66 Ϯ 0.77%), and retrograde transport (2.88 Ϯ 0.46%) compared with agematched WT DRG neurons (total mobility: 21.35 Ϯ 1.08%, p Ͻ 0.001; anterograde: 14.74 Ϯ 1.05%, p Ͻ 0.001; retrograde: 6.61 Ϯ 0.78%, p Ͻ 0.001) (Fig.…”
Section: G93asupporting
confidence: 81%
See 1 more Smart Citation
“…2C). Consistent with the axonal transport defects observed in embryonic motor neurons and adult DRG neurons (10,11,16), axonal mitochondria in SOD1 G93A DRG neurons showed reduced mobility (13.54 Ϯ 0.38%, mean Ϯ S.E. ), anterograde transport (10.66 Ϯ 0.77%), and retrograde transport (2.88 Ϯ 0.46%) compared with agematched WT DRG neurons (total mobility: 21.35 Ϯ 1.08%, p Ͻ 0.001; anterograde: 14.74 Ϯ 1.05%, p Ͻ 0.001; retrograde: 6.61 Ϯ 0.78%, p Ͻ 0.001) (Fig.…”
Section: G93asupporting
confidence: 81%
“…Mitochondrial morphology and membrane dynamics, required for maintaining proper function, depend on proper mitochondrial mobility in neurons (50). Several studies have suggested that the onset of ALS symptoms is caused by alterations in mitochondrial transport induced by mutant SOD1 expression (10,11). In the SOD1 G93A mouse model, disease onset and motor neuron death is immediately preceded by the accumulation of dysfunctional mitochondria in the distal region of the axon near the neuromuscular junction.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we targeted mutant SOD1 to the IMS of NSC34 cells by using the cleavable yeast cytochrome b2 MTS. This resulted in mitochondrial fragmentation and alterations of mitochondrial dynamics in the neurites, as well as increased sensitivity to metabolic and oxidative stress conditions (38).…”
mentioning
confidence: 99%
“…Though SOD1 is primarily a cytosolic protein, its partial deposition in the mitochondrial intermembrane space was shown to lead to mitochondrial dysfunction in mutant SOD1 transgenic mice (Magrane et al, 2009). The presence of damaged mitochondria is a pathological common finding in ALS MNs that may be associated to impaired autophagy-lysosomal system.…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%